Postoperative diaphragmatic hernia with upside-down stomach: a case report. Issue 8 (August 2022) - Wakabayashi, Masakazu; Kobori, Shuichi; Aoki, Kana; Yoshida, Hayato; Minoshima, Kou; Kimura, Tomohiro; Domoto, Yoshinori; Hosaka, Miki; Ushiku, Hideki; Funatsu, Kentarou; Aisaki, Kazuo
A 31-year-old man presented to our hospital's Emergency Department with sudden epigastric pain and vomiting. He had undergone endoscopic resection via the retroperitoneal route for a retroperitoneal tumor located in the left diaphragmatic crus of the esophageal hiatus at another hospital 8 months previously. Radiography and computed tomography showed inversion of the stomach beyond the diaphragm into the thoracic cavity, with the gastroesophageal junction serving as the fulcrum point. This finding led to a diagnosis of postoperative diaphragmatic hernia accompanied by an upside-down stomach (UDS). The prolapsed stomach in the thoracic cavity was reduced to the abdominal cavity using laparoscopic surgery. The postoperative course was favorable, and the patient was discharged from the hospital on postoperative day 7. No recurrence has been observed in the past 5 years. The pathological condition of a UDS observed in esophageal hiatal hernias may be found in postoperative diaphragmatic hernias. Laparoscopic surgery for a postoperative diaphragmatic hernia with a UDS is considered a useful surgical procedure. Laparoscopic surgery can simultaneously confirm the viability of the herniated organs, reduce the organs to the abdominal cavity, and close and reinforce the diaphragm.